The late presentation of postero-lateral congenital diaphragmatic hernias. Issue 800 (June 1992) - Heaton, N. D.; Adam, G.; Howard, E. R.
Abstract : Four patients presenting after the neonatal period with a combination of respiratory and gastro-intestinal symptoms and signs which point to the diagnosis of congenital postero-lateral diaphragmatic hernias are discussed. Late presentation is more common than previously acknowledged. Early correct diagnosis and treatment are associated with an excellent clinical outcome.